(untitled) (Bulletin KNOB, 2004)
This article focuses on the so-called ’Eppo stone’: a beautifully hewn tomb-cover dating from the middle of the fourteenth century with a detailed, realistic representation of a young man that is unparalleled in the entire Frisian coastal region. The stone originates from the village of Rinsumageest, near Dokkum, where it was fixed to the north-east side of the church until the middle of the nineteenth century. At the moment the stone is in the depot of the Fries Museum. For the interpretation of the edge inscription and the description of the figure one used to rely on the article devoted to the subject by the erudite L.J.F. Janssen in 1865. Upon closer examination it appears that some major corrections can be made in his text and the representation also reveals details that were not noticed before. The depiction of a jumping pole in the hands of the young man, for instance, indicates a specific regional Frisian context. However, the main point is that it was possible to establish the exact names of Eppo’s parents and brothers, from which it can be concluded that his family had better be placed among the nobility of northern Oostergo. This confirms the assumption that it concerns ancestors of the owners of the country estate ’Tjaardastate’, whom we did not know by name until the fifteenth century. The question whether the stone used to cover a sarcophagus and where that sarcophagus was originally placed, cannot be answered yet. At the end of the article it is suggested that the stone coffin had been interred in the crypt of the church of Rinsumageest; a crypt that may date from the twelfth century and was possibly used in the fourteenth century by the dominant noble family in the village in memory of themselves.